The study of the water regulation mechanisms in the winter bread wheat varieties under an acute drought - V. А. Golubova; V. L. Gaze (Зерновое хозяйство России)
Water regime of plants, characteristic of a certain variety, largely determines the resistance of plants to drought. Drought affects, first of all, such indicators as water absorption capacity, water retention capacity, water deficit and changes in total water content in the process of ontogenesis. Studying and taking into account a number of parameters of water regime can significantly increase the reliability of the assessment of plants for drought resistance. The purpose of the current study was to investigate the water regime of the winter bread wheat varieties under an acute drought and to select promising samples for breeding for drought resistance. The objects for the study were 7 winter bread wheat varieties developed by the FSBSI “Agricultural Research Center “Donskoy”. The study was carried out on the experimental plot (zasushnik) of the laboratory for plant physiology under an acute drought of 30% PV in 2017–2019. According to the study results, there have been identified the varieties ‘Zhavoronok’, ‘Volnitsa’ and ‘Volny Don’, which were characterized by the largest increase in water-absorbing capacity (from 40.0 to 41.1%); by a minimum increase in water deficit (1.3–2.1%); by the smallest decrease (3.2–3.8%) in the total water content in fibers due to adaptability to water stress conditions in spite of increasing drought. There has been recommended to introduce these samples into the breeding process aimed at developing drought-resistant winter bread wheat varieties.